Numerical modeling of complex plastic deformation of metals along plane and spatial trajectories of arbitrary curvature and torsion - Volkov, Ivan Andreevich; Korotkih, Yury Georgievich; Fomin, Mikhail Nikolaevich (Computational Continuum Mechanics, 2009)
The mathematical model of thermoplasticity describing the processes of complex plastic deformation of structural materials (metals and their alloys) along plane and spatial trajectories of arbitrary curvature and torsion is developed. For evaluating the adequacy degree of constitutive relations of elastoplasticity and the range of their applicability, numerical investigations of complex plastic deformation (by the example of steel 45) along the trajectories having the form of a circle and the screw trajectories of constant curvature and torsion are carried out. The obtained numerical results are compared with the data of full-scale experiments. It is shown that the developed model of thermoplaciticity describes qualitatively and quantitatively the main effects of complex plastic deformation of metals under arbitrary non-proportional combined (P-q-M) force loading.